If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3 = 2 + 7x Reorder the terms: -3 + 8x = 2 + 7x Solving -3 + 8x = 2 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -3 + 8x + -7x = 2 + 7x + -7x Combine like terms: 8x + -7x = 1x -3 + 1x = 2 + 7x + -7x Combine like terms: 7x + -7x = 0 -3 + 1x = 2 + 0 -3 + 1x = 2 Add '3' to each side of the equation. -3 + 3 + 1x = 2 + 3 Combine like terms: -3 + 3 = 0 0 + 1x = 2 + 3 1x = 2 + 3 Combine like terms: 2 + 3 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| 1-2x=3x-54 | | 21-7(19-x^2+6)-3x^2+1=0 | | -5/3v+4/3=-4v-4/5 | | 4x=3(4)-7 | | 1/3x12+7 | | 6x+8x-36=3+5x | | z+1.7=-18.1 | | (P+5)(p+2)=0 | | 7x+7=6x+5 | | x-0.2x=45 | | 4s^4+16s=0 | | 4x-5=2x+-7 | | -1/4v-4=5/3v-5/3 | | 8(6x+15)=30 | | -5x-10=3x-18 | | -3(5t-10)=67 | | 11x-men(7x-8)=44 | | -2m+1/3m=3/2m-1 | | 3yx-1x=2y-1 | | 3/4p=46.50 | | 13-x/2=x-1/2 | | 7x-8=5-6x | | 1/5=-3/2x-4/7 | | 3p^2-11p-8=0 | | 1/4(20) | | 6x+4x+9=11 | | 6x+16.2=21 | | 1.6s=5+1.5s-75 | | 8-8+8=8 | | 8-4x-7x=8 | | 3x+5=11+5x | | -9(v+4)+3v+7=7v+8 |